Percutaneous screw fixation for scaphoid non-union - Khan, Nabil Ali (My University, 2017)
design: A retrospective study of all scaphoid non-unions treated with percutaneous screw fixation at the Rosebank Hospital. Background: The Scaphoid plays a key role in the stability of the wrist joint, it acts as a strut bridging both carpal rows and is therefore continuously subjected to shearing and bending forces.[Abbreviated Abstract. Open document to view full version]
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand in partial fulfillment of the requirements for the Degree of Master of Medicine in the branch of Orthopaedic Surgery. Johannesburg,2017.
Keywords: Percutaneous Screw Fixation; Scaphoid Bone